Magnolia (Magnoliaceae) in Honduras: a synopsis with six new taxa - Vázquez-García, J. Antonio; Kelly, Daniel L.; Mejía-Valdivieso, Darío A.; Morales, Wilson; Dahua-Machoa, Alex; Vega-Rodríguez, Hermes; Ortega Peña, Alondra Salomé; Padilla-Lepe, Jesús; Muñiz-Castro, Miguel Á. (Phytotaxa, 2022)
We present a taxonomic synopsis for the ten species of Magnoliaceae from Honduras with a key and distribution map for the recognised species. Five new species and one new subspecies of Magnolia sect. Magnolia are described and illustrated: M. celaquensis, M. cusucoensis, M. darioi, M. pastorcortesii, M. picopijolensis, and M. sororum subsp. oligocarpa. The rediscovery of M. atlantida is confirmed after more than eight decades since its discovery in Atlántida, Honduras. The conservation status of each species is evaluated: one is considered least concern (LC), one vulnerable (VU), two endangered (EN) and six critically endangered (CR).